APPLICATION OF POLITE LANGUAGE TO EARLY CHILDHOOD CHARACTER EDUCATION IN PAUD BUAH HATI, CENTRAL ACEH DISTRICT - Suminah Suminah (JURNAL PAJAR (Pendidikan dan Pengajaran), 2020)
Early Childhood EducationBuah Hati implements character education which is packaged in polite language. Students who consist of various backgrounds, different age levels and different emotional levels, in their daily life the teacher speaks politely in interacting with students, which according to observations of  the teacher's language has an impact on every child's character. Education is very important for children or adults to get. Language is a very important communication tool, without language friendly communication will not be established. The purpose of this study is to find out how the concept of polite language towards character education and to know the application of polite language to character education for early childhood in PAUD Buah Hati. This research method is descriptive qualitative research that describes and explains facts in the field, primary and secondary data sources. The data collection process uses observation, interviews, documentation, data collection techniques with data collection, data reduction, data display, and conclusion drawing. The results of the research on the application of polite language, the categories of building communication are 80%, the type of good listener is 90%, the understanding of children's feelings is 86%, the active listener is 88%. Influence on children's character values in the categories of honesty 78%, 76% discipline, 75% tolerance, 85% confidence, 85% hard work, 79% responsibility and 80% manners. The conclusion in the study of the application of polite language to the character of children in PAUD Buah Hati, Central Aceh District, teachers treat children to build communication with children, become good listeners, understand children's feelings, and stage an active listener which has an impact on honesty, discipline, tolerance, confidence , Hard work, responsibility and courtesy.